Reception of Islamic Legal Rituals Among Indigenous Indonesian Communities with Comparative Findings from Wetu Telu and Masade - Yusuf, Nasruddin; Willya, Evra; Mash'ud, Imam; Kamma, Hamzah; Imamuddin, Imamuddin (IAIN Manado, 2025)
This article examines the Reception of Islamic legal rituals among indigenous Indonesian communities through a law-centered comparative design. This study understands reception as the selection, reinterpretation, and substantive integration of Islamic ritual norms into local practice. The framework juxtaposes doctrinal analysis of fiqh (Islamic jurisprudence) categories, namely ibādāt taʿabbudī/tawqīfī (worship rituals strictly bound to canonical pillars and conditions) and muʿāmalāt/ahwāl al-shakhṣiyyah (social transactions and personal status), with ethnographic and historical materials. The analysis assesses four equivalent domains: core obligations of worship, calendrical ordering, sacred space and authority, and life-cycle rites. Findings indicate that the Wetu Telu (Sasak